48th Don Carlos Palanca memorial awards for literature - Anonuevo, Ma. Luz Rebecca (Animo Repository, 1998)
Ma. Luz Rebecca Anonuevo, a Ph.D Literature student, grabbed the 1st prize for poetry in Filipino, Pagtingala: Pananahan at Paglalayag sa mga Tula ng Lagalag in the 48th Don Carlos Palanca Memorial Awards for Literature. Under the same category, former DLSU student Raymund Magno-Garlitos won the 3rd place for Kuwadernong Rosas ng Pagdating at Paglisan.